Asset specificity, inter-firm ecosystem, firm adaptability and supply chain integration - Nakayima, Farida; Namagembe, Sheila; Kabagambe, Levi; Ntayi, Joseph; Muhwezi, Moses (Emerald, 2024)
Purpose This study investigates the effect of asset specificity, inter-firm ecosystem and firm adaptability on supply chain integration. The study also investigates the mediation effect of firm adaptability on the relationship between asset specificity and supply chain integration and inter-firm ecosystem and supply chain integration. Design/methodology/approach This research applied a quantitative research methodology to investigate the interdependencies between study variables. A disproportionate stratified simple random sampling technique was used to select the firms that participated in the study. As a result, 103 food processing firms were selected from a total population of 345 firms located in Kampala district. Findings The findings reveal that the direct relationship between asset specificity and supply chain integration and inter-firm ecosystem and supply chain integration was found positive but insignificant. Both asset specificity and inter-firm ecosystem are associated positively with firm adaptability. A partial mediation was established between asset specificity and SCI while a full mediation effect was found in inter-firm ecosystem and SCI. Research limitations/implications The study used perceptual measures to obtain responses on the various constructs investigated and how these constructs relate. To avoid biasing the results, key suppliers and customers were not involved due to multi-level relationships that they maintain with various firms. Originality/value This study contributes to existing studies by applying two theories. First, the study applies the Transaction Cost Theory to study the effect of asset specificity on supply chain integration. Secondly, the Complexity Adaptive System Theory was applied to examine the influence of firm adaptability and inter-firm ecosystem on supply chain integration. Few studies have focused on the effect of inter-firm ecosystem in the supply chain; yet, SCI involves network of various player making supply chains complex This study is among the few studies that have focused on adaptability in the food processing sector in a developing country like Uganda.